Association of worker characteristics and early reimbursement for physical therapy, chiropractic and opioid prescriptions with workers' compensation claim duration, for cases of acute low back pain: an observational cohort study. Issue 8 (26th August 2015) - Busse, Jason W; Ebrahim, Shanil; Heels-Ansdell, Diane; Wang, Li; Couban, Rachel; Walter, Stephen D
Abstract : Objective: To assess the association between early reimbursement for physiotherapy, chiropractic and opioid prescriptions for acute low back pain (LBP) with disability claim duration. Design: Observational cohort study. Setting and participants: From a random sample of 6665 claims for acute, uncomplicated LBP approved by the Ontario Workplace Safety and Insurance Board (WSIB) in 2005, we analysed 1442 who remained on full benefits at 4 weeks after claim approval. Primary outcome measure: Our primary outcome was WSIB claim duration. Results: We had complete data for all but 3 variables, which had <15% missing data, and we included missing data as a category for these factors. Our time-to-event analysis was adjusted for demographic, workplace and treatment factors, but not injury severity, although we attempted to include a sample with very similar, less-severe injuries. Regarding significant factors and treatment variables in our adjusted analysis, older age (eg, HR for age ≥55 vs <25=0.52; 99% CI 0.36 to 0.74) and WSIB reimbursement for opioid prescription in the first 4 weeks of a claim (HR=0.68; 99% CI 0.53 to 0.88) were associated with longer claim duration. Higher predisability income was associated with longer claim duration, but only among persistent claims (eg, HR for active claims at 1 year with a predisability income >920 vs ≤480/week=0.34; 99% CI 0.17 to 0.68). Missing data for union membership (HR=1.27; 99% CI 1.01 to 1.59), and working for an employer with a return-to-work programme were associated with fewer days on claim (HR=1.78; 99% CI 1.45 to 2.18). Neither reimbursement for physiotherapy (HR=1.01; 99% CI 0.86 to 1.19) nor chiropractic care (HR for active claims at 60 days=1.15; 99% CI 0.94 to 1.41) within the first 4 weeks was associated with claim duration. Our meta-analysis of 3 studies (n=51 069 workers) confirmed a strong association between early opioid use and prolonged claim duration (HR=0.57, 95% CI 0.48 to 0.69; low certainty evidence). Conclusions: Our analysis found that early WSIB reimbursement for physiotherapy or chiropractic care, in claimants fully off work for more than 4 weeks, was not associated with claim duration, and that early reimbursement for opioids predicted prolonged claim duration. Well-designed randomised controlled trials are needed to verify our findings and establish causality between these variables and claim duration.